A high-resilience environmentally friendly EVA composite foam material, preparation method and application thereof
By developing high-resistance environmentally friendly EVA composite foaming materials and combining modified leather powder with other polymer materials, the existing foamed sole materials are solved and environmentally friendly, carbon reduction and performance improvement effects are achieved.
Patent Information
- Application Number
- CN202411661221.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Existing foamed sole materials are not friendly to environmental protection and are difficult to effectively utilize a large amount of leather waste, resulting in environmental pollution and waste of resources.
Develop a high-resistance environmentally friendly EVA composite foaming material. By combining modified leather powder with other polymer materials, it uses ethylene-vinyl acetate copolymer and other materials to foam to form a lightweight, wear-resistant and excellent rebound performance.
The goal of environmental protection and carbon reduction has been achieved. By utilizing leather waste, the dependence on non-renewable petroleum products is reduced, harmful gas emissions in the production process are reduced, and the material's wear resistance and rebound properties are significantly improved.
Smart Images

Figure CN119144081B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of footwear foaming materials, and in particular to a high-resilience environmentally friendly EVA composite foaming material, a preparation method and application thereof. Background Art
[0002] At present, most of the foam soles are made of materials such as ethylene-vinyl acetate copolymer (EVA), and are formed by foaming. They have excellent elasticity and anti-aging performance characteristics. However, the common foam sole resin materials are chemically synthesized materials, and there is room for improvement in environmental protection.
[0003] According to relevant data, my country is the world's largest leather producer and consumer, with 1.4 million tons of leather waste produced each year, and Jinjiang's leather industry accounts for nearly 10% of the country's total. A large amount of leather waste brings high solid waste disposal costs to tannery and shoemaking companies. Five years ago, the state included chromium-containing leather scraps and leather edges in the list of hazardous wastes, prohibiting landfill and incineration, which means that how to deal with my country's annual 2 million tons of leather waste has become a difficult problem.
[0004] Therefore, developing an environmentally friendly EVA sole composite foam material can not only meet the needs of consumers to maintain the physical properties of the foam material during reciprocating motion and ensure continuous comfort, but also can make large-scale use of leather waste, protect the environment, and reduce the generation of environmentally harmful substances from waste leather. At the same time, seeking the recycling of leather waste is one of the current trends in sustainable development. Summary of the invention
[0005] In view of this, the present invention provides a high-resilience environmentally friendly EVA composite foam material, a preparation method and application thereof. The EVA composite foam material provided by the present invention is used as a shoe midsole, which has the characteristics of light weight, good wear resistance, excellent rebound performance, etc., and can achieve certain environmental protection and carbon reduction purposes, which is conducive to achieving sustainable development.
[0006] The present invention provides a high-resilience environmentally friendly EVA composite foam material, which is prepared by foaming an EVA composite material, wherein the EVA composite material comprises the following components in parts by weight:
[0007] 40-50 parts of ethylene-vinyl acetate copolymer, 15-25 parts of polyolefin elastomer, 10-30 parts of olefin block copolymer, 5-10 parts of EPDM rubber, 5-10 parts of anti-wear agent, 3-5 parts of modified leather powder, 1.5-2.5 parts of modified hydrogenated resin, 0.2-0.5 parts of stearic acid, 0.2-1 parts of zinc stearate, 1.2-2 parts of zinc oxide, 0.3-0.8 parts of odorless bridging agent, 4-6 parts of AC foaming agent;
[0008] The modified leather powder is obtained by surface-modifying low-temperature ground waste leather powder with N-aminoethyl-3-aminopropylmethyldimethoxysilane; and the modified hydrogenated resin is formed by mixing polyethylene glycol and hydrogenated resin raw materials.
[0009] Accordingly, the embodiment of the present invention provides a method for preparing the high-resilience environmentally friendly EVA composite foam material as described above, comprising the following steps:
[0010] The components except the odorless bridging agent and the AC foaming agent are mixed according to the mass fraction to obtain a first mixed product; the first mixed product is mixed with the odorless bridging agent and the AC foaming agent to obtain a second mixed product; the second mixed product is granulated and then subjected to an injection foaming process or a secondary compression molding foaming process to obtain the high-resilience environmentally friendly EVA composite foaming material.
[0011] For leather with a lifespan of more than 50 years, chemically treated leather products can last even longer; thicker leather on shoes also takes longer to decompose, taking about 80 years.
[0012] Animal leather has irregular shapes. Workers will try to use the whole piece of leather as much as possible, and the scraps will be discarded as garbage. The smell of leather is non-toxic, but burning leather is harmful to the human body. Leather contains ingredients such as benzene and formaldehyde. After burning, a large amount of harmful gases such as dioxins will be produced. These gases are the culprits of tumors and leukemia. There are no harmful gases when the leather itself is burned, but a large amount of chemical reagents such as aniline dyes and chromium salts are used in the leather processing process. During the combustion process, nitrogen compounds (nitric oxide, nitrogen dioxide), sulfur dioxide and other harmful and irritating gases will be released, and the leather is prone to cracking. The combustion of polyurethane (PU) leather will produce some harmful and irritating plastic gases, such as hydrogen cyanide, carbon monoxide, ammonia, nitrogen-containing compounds (nitric oxide, nitrogen dioxide, etc.), etc. The production and combustion process of polyvinyl chloride (PVC) leather will produce dioxins and hydrogen chloride; dioxins and hydrogen chloride are highly toxic substances that may cause cancer and other diseases, and will produce a strong irritating plastic odor (the main odor comes from solvents, coating agents, fatliquors, plasticizers and mildew inhibitors, etc.).
[0013] The embodiment of the present invention is to grind discarded leather scraps and leather scraps into powder using liquid nitrogen and low temperature, and then produce the required modified leather powder through surface modification. The low temperature grinding process reduces heat generation, and thus no harmful gas caused by burning leather is generated, which is environmentally friendly; and the modified leather powder is conducive to the preparation of foaming materials with good performance.
[0014] In a specific embodiment of the present invention, the modified leather powder is obtained by the following operation: waste leather is cryogenically frozen by liquid nitrogen and sprayed with airflow, and then cryogenically ground to obtain waste leather powder; the waste leather powder is surface-modified by using N-aminoethyl-3-aminopropylmethyldimethoxysilane to obtain the modified leather powder.
[0015] In the embodiment of the present invention, discarded leather scraps and leather scraps from the production process of leather factories are used as waste leather materials. After the large pieces of leather scraps are cut, they are added into a low-temperature three-stage cyclone centrifuge, and the leather scraps and leather scraps are frozen and hardened by low-temperature freezing of liquid nitrogen, and particles (i.e., colorless crystal silicon carbide corundum with a density of 3.06-3.20 g / m3) are sprayed through a high-speed airflow. 3 ; Very hard, about 9.5 on the Mohs scale), hit leather scraps and leather shavings, thus efficiently and accurately turning waste leather into smaller leather shavings; Separate leather shavings and silicon carbide through a centrifuge, and then transport the separated leather powder to a low-temperature grinder, preferably grinding into 120-mesh waste leather powder. During the processing, the whole process is at low temperature, and no harmful gases are generated. The low-temperature processed powder is then dried and set aside.
[0016] In the embodiment of the present invention, the processed waste leather powder is surface-modified using N-aminoethyl-3-aminopropylmethyldimethoxysilane to obtain the modified leather powder. The structural formula of the N-aminoethyl-3-aminopropylmethyldimethoxysilane is as follows, which is also called silane coupling agent KH-562; the leather modified with KH562 has better coating properties, making the modified leather powder more fusion with other polymer materials. Preferably, the particle size of the modified leather powder can be 120-150 meshes.
[0017] .
[0018] The embodiment of the present invention modifies the waste leather powder to increase the contact angle of the leather powder (it can be modified to a contact angle of 90° to increase the specific surface area of the leather powder) to increase the surface compatibility and adhesion performance of organic materials and inorganic materials, increase the affinity of the material, and add it to the high-rebound, tear-resistant, environmentally friendly EVA composite sole foaming material, which helps to improve the wear resistance and rebound performance of the material while reducing the specific gravity of the material.
[0019] The embodiment of the present invention adopts the EVA composite material formula added with the modified leather powder to prepare the EVA composite foaming sole material. In parts by weight, the EVA composite material formula mainly includes: 40-50 parts of ethylene-vinyl acetate copolymer (EVA), 15-30 parts of polyolefin elastomer, 10-26 parts of olefin block copolymer, 4-10 parts of ethylene propylene diene monomer rubber, and 3-5 parts of modified leather powder.
[0020] Wherein, the ethylene-vinyl acetate copolymer is the main resin material, and the mass parts can be 40 parts, 42 parts, 45 parts, 50 parts, etc. Further, the molar content of vinyl acetate in the ethylene-vinyl acetate copolymer is between 26% and 40%, which is conducive to improving flexibility, impact resistance, etc. The ethylene-vinyl acetate copolymer adopts a commercially available product, and the model can be Taiwan Formosa Plastics EVA7470M, EVA7350M, EVA7360M, which has good plasticity, elasticity and foamability, can resist the action of external forces to a certain extent, and has high tensile strength and elongation at break; it can also be EVA40L-03 produced by DuPont in the United States, and EVA40W produced by Dow in the United States. 40L-03 and 40W have high VA content, which makes the material have good softness and retractile properties, and can be applied to the bonding requirements of various complex angles and curved surfaces, and can achieve firm bonding between a variety of different materials and maintain viscosity for a long time.
[0021] The polyolefin elastomer is commonly known as POE, which is a thermoplastic elastomer produced by DOW Chemical Company of the United States using metallocene as a catalyst and has a narrow relative molecular weight distribution and a uniform short chain branch distribution; it is preferably 15-25 parts or 20-30 parts. The content of 1-octene in the polyolefin elastomer is generally 20%-30%, and the density can be 0.87-0.91g / cm 3 . Furthermore, the model of the polyolefin elastomer is one or more of ENGAGE 8150, ENGAGE 8450, ENGAGE 8480, and ENGAGE 8003. POE material is an ethylene-α-olefin copolymer elastomer structure, wherein α-olefin refers to a monoolefin with a double bond at the end of the molecular chain. Common commercial α-olefins include α-butene (4C), α-hexene (6C), α-octene (8C) and propylene. There are two main types of basic structures of POE: one is the 8C structure composed of ethylene and octene, and the other is the 4C structure composed of ethylene and butene. The preferred structure used in the present invention is the 8C structure.
[0022] The role of POE in EVA composite foaming is mainly reflected in improving the pore morphology of the foamed product, improving the physical and mechanical properties of the material, as well as elasticity, wear resistance, chemical corrosion resistance, etc. These properties are maintained and enhanced during the foaming process, so that the foamed product exhibits better durability and comfort during use. The POE indicators specifically used in the embodiment of the present invention include: hardness 70-90°A, density 0.868-0.902g / cm 3 , tensile strength 15-25mpa, tear 70-90N / mm.
[0023] The olefin block copolymer is referred to as OBC, which has balanced advantages in flexibility and heat resistance. The EVA composite material preferably includes 15 to 26 parts of olefin block copolymer, more preferably 18 to 25 parts; further, the model of the olefin block copolymer is one or more of Infuse9100, Infuse9107, Infuse9500, and Infuse9507 (Dow Chemical Company, USA). The molecular structure of OBC consists of two parts: a crystallizable ethylene-octene segment (hard segment) with a low comonomer content and a high melting temperature, and an amorphous ethylene-octene segment (soft segment) with a high comonomer content and a low glass transition temperature. This structure makes OBC perform well at high temperatures, and at the same time has better elastic recovery and compression deformation properties at both room temperature and high temperatures. In a specific embodiment of the present invention, the parameters of the OBC involved include: hardness 60-75°A, density 0.866-0.877g / cm 3 , tensile strength 5-9mpa, tear 35-50N / mm.
[0024] In addition, the EVA composite material includes 4 to 10 parts of EPDM rubber components, preferably 4 to 6 parts by mass; the EPDM rubber is a terpolymer elastomer of ethylene, propylene and non-conjugated dienes. Furthermore, the model of the EPDM rubber is one or more of 3745P (produced by Dow Chemical Company, USA), 3092P (produced by Sinopec and Mitsui), and 3722 (produced by Dow Chemical Company, USA). The hardness of the EPDM used in the embodiment of the present invention is 60-65°A, and the density is 0.86-0.875g / cm 3 , tensile strength: 2-3mpa, tear: 10-15N / mm; ethylene content 50-65%, Mooney viscosity ML125℃1+455-65, ENB (ethylidene norbornene): 3-5wt%.
[0025] Adding 3 to 5 parts of the modified leather powder to the EVA composite material is beneficial to improving the high wear resistance and high resilience of the foamed sole material, so that it can directly touch the ground without being attached to the rubber sole. In addition, the embodiment of the present invention includes 5 to 10 parts of a wear-resistant agent and 1.5 to 2.5 parts of a modified hydrogenated resin, wherein the modified hydrogenated resin is formed by mixing polyethylene glycol and a hydrogenated resin raw material.
[0026] Furthermore, the modified hydrogenated resin is formed by mixing polyethylene glycol with a molecular weight of 3000-5000 and a hydrogenated resin raw material in a mass ratio of 0.5-2:1. The preparation of the modified hydrogenated resin is preferably as follows: the hydrogenated resin raw material and the polyethylene glycol with a molecular weight of 4000 are finely ground and fully mixed in a ratio of 1:1; the powder after the uniform mixing is the modified hydrogenated resin.
[0027] Hydrogenated resin is a resin whose molecular structure is changed by hydrogenation reaction. It is usually obtained by hydrogenation reaction of polymer compounds such as unsaturated polyester, polyether, polyamide, etc. The specific hydrogenated resin used is hydrogenated C5 petroleum resin. C5 resin is obtained by cationic polymerization of C5 fraction decomposed from naphtha. Its components include isobutylene, 1,3-dipentene, methylbutene, pentene, cyclopentadiene, pentane, cyclopentane, etc. The modified hydrogenated resin is mixed with polyethylene glycol. The introduction of hydroxyl groups can increase the polarity of resin molecules and improve the surface tension, wettability and flowability of the resin; at the same time, the introduction of hydroxyl groups can also form a cross-linked structure, improve the compatibility of leather powder and polymer, improve the bonding strength between the foamed midsole and the rubber outsole (RB sole), and greatly improve the bonding strength between the sole and the upper.
[0028] The modified hydrogenated resin described in the embodiment of the present invention has a great effect on improving the durability of the material, which enables the leather powder and the high molecular polymer to be compatible for a long time. The modified hydrogenated resin can also improve the appearance of the product, making it more beautiful, and can make the surface of the composite foam material after adding the modified leather powder more uniform and smooth, thereby improving its texture and appearance.
[0029] The weight percentage of the anti-wear agent is preferably 8-10 parts; the anti-wear agent is preferably a vinyl silicone composite anti-wear agent, which further improves the wear resistance and other properties. Specifically, the anti-wear agent is a 108E model product produced by Xiamen Boshiyuan Company.
[0030] The material composition of the EVA composite foaming material described in the embodiment of the present invention includes: 0.2~0.5 parts of stearic acid, 0.2~1 parts of zinc stearate, 1.2~2 parts of zinc oxide, 0.3~0.8 parts of odorless bridging agent, and 4~6 parts of AC foaming agent. Among them, stearic acid is preferably 0.3~0.4 parts; zinc stearate is preferably 0.5~0.6 parts; zinc oxide is preferably 1.2~1.5 parts, which is conducive to cross-linking foaming and lubrication. The odorless bridging agent is also called an odorless cross-linking agent, mainly di-tert-butyl peroxide diisopropylbenzene, referred to as BIPB, BIBP or odorless DCP. The chemical name of the AC foaming agent is azodicarbonamide, which is non-toxic and widely used as a foaming agent. In some embodiments, the odorless bridging agent is 0.5~0.6 parts; the AC foaming agent is 5~5.5 parts.
[0031] In a specific embodiment of the present invention, the preparation method of the high-resilience environmentally friendly EVA composite foam material comprises the following steps:
[0032] Step 1: Weigh the formula materials according to the mass parts of each component in the composition material for preparing the high-resilience EVA foam material defined above;
[0033] Step 2: Mix all the components weighed except the cross-linking agent and the foaming agent; the mixing time may be 5-10 minutes, and the temperature may be 105-115°C;
[0034] Step 3: adding weighed cross-linking agent and foaming agent to the mixed material, and then mixing;
[0035] Step 4: Granulate the obtained mixed material, and place the granules to cool;
[0036] In order to make the formula material usable in a wider range, the next step adopts the MD secondary molding process to prepare the environmentally friendly high-resilience EVA foam material sole and test piece; the embodiment of the present invention is not limited to this foaming process, and can also be an injection foaming process.
[0037] Step 5: Weigh a certain mass of particles from step 4 according to the mold shape, and perform small foaming to obtain a rough embryo (foaming at a rate of 1.7-1.8%); the temperature of the small foaming equipment is preferably 165-175°C, and the pressure is 150-170kg / cm 2 , MD small foaming time is 600-650 seconds.
[0038] Step 6: The small foamed rough blank in step 5 is subjected to hot pressing and cooling to obtain the EVA foamed material sole and test piece. This can be carried out in an MD molding machine, with the hot pressing temperature preferably being 155-165°C and the cooling temperature being 11-17°C.
[0039] In the embodiment of the present invention, the density of the high resilience environmentally friendly EVA composite foam material can be 0.17-0.20 g / cm 3 , the hardness can be 45-50 Asker C; the EVA composite foam material is light, has high resilience, good wear resistance, has certain green environmental protection performance, and can be used as a sole material, etc. Further, the embodiment of the present invention provides the use of the high-resilience environmentally friendly EVA composite foam material as described above as a midsole in the preparation of shoes, and the average thickness of the midsole can be 11-13 mm.
[0040] In summary, the embodiment of the present invention uses the EVA composite material containing modified leather powder as the raw material formula, and obtains the high-resilience environmentally friendly EVA composite foam material by foaming. Among them, the embodiment of the present invention uses discarded leather scraps, and produces the required powders of different mesh sizes by low-temperature freezing and low-temperature grinding with liquid nitrogen. During the production process, a large amount of harmful gases such as dioxins will not be generated due to high temperature, and non-renewable petroleum products are not added to achieve the purpose of environmental protection. In addition, the embodiment of the present invention increases the affinity of leather powder and high molecular polymers by modification to improve the wear resistance of EVA composite foam materials. The embodiment of the present invention also adopts the addition method of modified hydrogenated resin, which can disperse the hydroxyl groups of polyethylene glycol in the matrix material of hydrogenated resin, provide a larger specific surface area, increase the interaction force, give the material better wear resistance, increase the self-adhesiveness and mutual adhesion of the material, and improve the bonding strength of the sole fitting. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a scanning electron microscope photograph of the foamed composite material obtained in Example 1 at a magnification of 12.0 mm × 250X;
[0042] Figure 2 This is a scanning electron microscope photograph of the foamed composite material obtained in Example 1 at a magnification of 12.0 mm×500X;
[0043] Figure 3 This is a scanning electron microscope photograph of the foamed composite material obtained in Example 1 at a magnification of 11.9 mm × 2000X;
[0044] Figure 4 This is a scanning electron microscope photograph of the foamed composite material obtained in Comparative Example 2 at a magnification of 12.9 mm × 20000X;
[0045] Figure 5 This is a scanning electron microscope photograph of the foamed composite material obtained in Example 2 at a magnification of 12.9 mm × 250X;
[0046] Figure 6 This is a scanning electron microscope photograph of the foamed composite material obtained in Example 2 at a magnification of 12.9 mm × 500X;
[0047] Figure 7 This is a scanning electron microscope photograph of the comparative example Sande foamed composite material at a magnification of 12.8 mm × 2000X;
[0048] Figure 8 This is a scanning electron microscope photograph of the foamed composite material obtained in Comparative Example 3 at a magnification of 12.8 mm×8000X. DETAILED DESCRIPTION
[0049] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.
[0050] In order to further understand the present invention, the present invention is described in detail below in conjunction with the examples, and the protection scope of the present invention is not limited by the following examples. In the examples, each raw reagent and material can be obtained commercially, and the experimental method without specifying the specific experimental conditions is a conventional method and condition well known in the art. The preparation of the modified leather powder and modified hydrogenated resin used is as follows:
[0051] The waste leather was cryogenically frozen by liquid nitrogen and sprayed with air flow, and then cryogenically ground to obtain 120-mesh waste leather powder; the waste leather powder was surface-modified by using N-aminoethyl-3-aminopropylmethyldimethoxysilane to obtain (modified to a contact angle of 90°).
[0052] The hydrogenated resin raw material (hydrogenated C5 petroleum resin) and polyethylene glycol (PEG4000) with a molecular weight of 4000 are weighed in a ratio of 1:1, crushed into fine powder in a grinder, and stirred to mix evenly; the powder after mixing evenly is the modified hydrogenated resin.
[0053] Embodiment 1 (MD)
[0054] A lightweight, wear-resistant, high-resilience and environmentally friendly EVA composite foam material and a preparation method thereof, which is prepared by foaming an EVA composite material; the EVA composite material comprises the following components in parts by weight:
[0055] Ethylene-vinyl acetate copolymer: 50 parts, polyolefin elastomer: 25 parts, olefin block copolymer: 20 parts, EPDM rubber: 5 parts, wear resistance agent: 8 parts, modified leather powder: 3.5 parts, modified hydrogenated resin: 2 parts, stearic acid: 0.3 parts, zinc stearate: 0.5 parts, zinc oxide: 1.2 parts, odorless bridging agent: 0.5 parts, AC foaming agent: 5 parts.
[0056] The preparation method comprises the following steps:
[0057] 1) Weigh the following ingredients by mass: 50 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 20 parts of olefin block copolymer, 5 parts of EPDM rubber, 8 parts of wear resistance agent, 0.3 parts of stearic acid, 0.5 parts of zinc stearate, 1.2 parts of zinc oxide, 3.5 parts of modified leather powder, and 2 parts of modified hydrogenated resin.
[0058] 2) kneading all the ingredients weighed in step 1) for 5-10 minutes at a temperature of 105-115°C;
[0059] 0.5 parts of odorless bridging agent and 5 parts of AC foaming agent were added to the kneaded mixture, and the mixture was kneaded again.
[0060] 3) Granulate the mixture obtained in step 2) for 9-11 minutes at a temperature of 100° C.-105° C. and store for 24 hours for use.
[0061] 4) Pour the particles obtained in step 3) into the required small foaming mold for foaming (technical parameters of small foaming process: temperature 170±5℃, lower foaming machine pressure 165kg / cm 2 , foaming molding time 620±10 seconds, the same as in the following embodiments);
[0062] 5) Clean the small foams prepared in step 4) and store them for 12 hours, then put them into the MD molding machine for heating for 420 seconds and cooling for 420 seconds (the temperature of the MD molding machine is 155-165°C, and the cooling temperature is 11-17°C) to obtain a lightweight, wear-resistant, high-resilience, and environmentally friendly EVA composite foam MD sole.
[0063] Embodiment 2 (MD)
[0064] The present invention provides a lightweight, wear-resistant, high-rebound and environmentally friendly EVA composite foam material and a preparation method thereof, which is prepared by foaming an EVA composite material; the EVA composite material comprises the following components in parts by weight:
[0065] Ethylene-vinyl acetate copolymer: 40 parts, polyolefin elastomer: 30 parts, olefin block copolymer: 26 parts, EPDM rubber: 4 parts, wear resistance agent: 8.5 parts, modified leather powder: 4 parts, modified hydrogenated resin: 3.5 parts, stearic acid: 0.3 parts, zinc stearate: 0.5 parts, zinc oxide: 1.2 parts, odorless bridging agent: 0.52 parts, AC foaming agent: 5.1 parts.
[0066] The preparation method comprises the following steps:
[0067] 1) Weigh the following ingredients by mass: 40 parts of ethylene-vinyl acetate copolymer, 30 parts of polyolefin elastomer, 26 parts of olefin block copolymer, 4 parts of EPDM rubber, 8.5 parts of anti-wear agent, 0.3 parts of stearic acid, 0.5 parts of zinc stearate, 1.2 parts of zinc oxide, 4 parts of modified leather powder, and 3.5 parts of modified hydrogenated resin.
[0068] 2) kneading all the ingredients weighed in step 1) for 5-10 minutes at a temperature of 105-115°C;
[0069] 0.52 parts of odorless bridging agent and 5.1 parts of AC foaming agent were added to the above mixture and then kneaded.
[0070] 3) Granulate the mixture obtained in step 2) for 9-11 minutes at a temperature of 100° C.-105° C. and store for 24 hours for later use.
[0071] 4) pouring the particles obtained in step 3) into a desired small foaming mold for foaming;
[0072] 5) Clean the small foams prepared in step 4) and store them for 12 hours, then put them into the MD molding machine for heating for 420 seconds and cooling for 420 seconds (the temperature of the MD molding machine is 155-165°C and the cooling temperature is 11-17°C) to obtain a lightweight, wear-resistant, high-resilience and environmentally friendly EVA composite foam MD sole.
[0073] Embodiment 3 (MD)
[0074] The present invention provides a lightweight, wear-resistant, high-rebound and environmentally friendly EVA composite foam material and a preparation method thereof, which is prepared by foaming an EVA composite material; the EVA composite material comprises the following components in parts by weight:
[0075] Ethylene-vinyl acetate copolymer: 45 parts, polyolefin elastomer: 25 parts, olefin block copolymer: 25 parts, EPDM rubber: 5 parts, wear-resistant agent: 10 parts, modified leather powder: 5 parts, modified hydrogenated resin: 3 parts, stearic acid: 0.3 parts, zinc stearate: 0.5 parts, zinc oxide: 1.5 parts, odorless bridging agent: 0.5 parts, AC foaming agent: 5.5 parts.
[0076] The preparation method comprises the following steps:
[0077] 1) Weigh the following ingredients by mass: 45 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 25 parts of olefin block copolymer, 5 parts of EPDM rubber, 10 parts of anti-wear agent, 0.3 parts of stearic acid, 0.5 parts of zinc stearate, 1.5 parts of zinc oxide, 5 parts of modified leather powder, and 3 parts of modified hydrogenated resin;
[0078] 2) kneading all the ingredients weighed in step 1) for 5-10 minutes at a temperature of 105-115°C;
[0079] 0.5 parts of odorless bridging agent and 5.5 parts of AC foaming agent were added to the above mixture and then kneaded.
[0080] 3) Granulate the mixture obtained in step 2) for 9-11 minutes at a temperature of 100° C.-105° C. and store for 24 hours for later use.
[0081] 4) pouring the particles obtained in step 3) into a desired small foaming mold for foaming;
[0082] 5) Clean the small foam prepared in 4) and store it for 12 hours, then put it into the MD molding machine for heating for 420 seconds, and cool it for 420 seconds (the temperature of the MD molding machine is 155-165℃, and the cooling temperature is 11-17℃), to obtain a lightweight, wear-resistant, high-rebound and environmentally friendly EVA composite foam material MD sole.
[0083] Comparative Example 1 (MD)
[0084] The traditional MD lightweight composite materials on the market include the following components by weight:
[0085] Polyolefin elastomer: 25 PHR, Ethylene-vinyl acetate copolymer: 50 PHR, Olefin block copolymer: 18 PHR, EPDM rubber: 7 PHR, Anti-wear agent: 6 PHR, Stearic acid: 0.2 PHR, Zinc stearate: 0.8 PHR, Zinc oxide: 1.0, Odorless bridging agent: 0.7 PHR, AC foaming agent: 4.8 PHR.
[0086] Prepare as follows:
[0087] 1) Weigh the following ingredients by mass: polyolefin elastomer 18 PHR; ethylene-vinyl acetate copolymer 50 PHR; olefin block copolymer 25 PHR; EPDM rubber 7 PHR; anti-wear agent: 6 PHR, stearic acid 0.2 PHR, zinc stearate 0.8 PHR;
[0088] 2) Mix all the ingredients weighed in step 1) for 10-15 minutes at a temperature of 115-125°C.
[0089] 3) Weigh the following ingredients by mass: odorless bridging agent: 0.7 PHR, AC foaming agent: 4.8 PHR;
[0090] 4) Add all the ingredients weighed in step 3) to the mixed material in step 2) and mix again. The mixing time is 5-7 minutes at a temperature of 130-135°C.
[0091] 5) Granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.
[0092] 6) pouring the particles obtained in step 5) into a desired small foaming mold for foaming;
[0093] 7) The small foam prepared in step 6) is cleaned and stored for 12 hours, then placed in an MD molding machine for heating for 420 seconds, and cooled for 420 seconds (the temperature of the MD molding machine is 155-165°C, and the cooling temperature is 11-17°C), to obtain a traditional lightweight foamed MD sole.
[0094] Comparative Example 2 (MD)
[0095] This comparative example is made of unmodified leather powder, and the EVA composite material includes the following components in parts by weight:
[0096] Ethylene-vinyl acetate copolymer: 45 parts, polyolefin elastomer: 25 parts, olefin block copolymer: 25 parts, EPDM rubber: 5 parts, wear-resistant agent: 10 parts, unmodified leather powder: 5 parts, modified hydrogenated resin: 3 parts, stearic acid: 0.3 parts, zinc stearate: 0.5 parts, zinc oxide: 1.5 parts, odorless bridging agent: 0.5 parts, AC foaming agent: 5.5 parts.
[0097] The preparation method comprises the following steps:
[0098] 1) Weigh the following ingredients by mass: 45 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 25 parts of olefin block copolymer, 5 parts of EPDM rubber, 10 parts of wear-resistant agent, 0.3 parts of stearic acid, 0.5 parts of zinc stearate, 1.5 parts of zinc oxide, 5 parts of unmodified leather powder, and 3 parts of modified hydrogenated resin;
[0099] 2) kneading all the ingredients weighed in step 1) for 5-10 minutes at a temperature of 105-115°C;
[0100] 0.5 parts of odorless bridging agent and 5.5 parts of AC foaming agent were added to the above mixture and then kneaded.
[0101] 3) Granulate the mixture obtained in step 2) for 9-11 minutes at a temperature of 100° C.-105° C. and store for 24 hours for later use.
[0102] 4) pouring the particles obtained in step 3) into a desired small foaming mold for foaming;
[0103] 5) The small foams prepared in step 4) are cleaned and stored for 12 hours, and then placed in an MD molding machine for heating for 420 seconds and cooled for 420 seconds (the temperature of the MD molding machine is 155-165°C, and the cooling temperature is 11-17°C) to obtain an EVA composite foam material MD sole.
[0104] Comparative Example 3 (MD)
[0105] This comparative example is not made using the modified hydrogenated resin of the present invention, and the EVA composite material includes the following components in parts by weight:
[0106] Ethylene-vinyl acetate copolymer: 45 parts, polyolefin elastomer: 25 parts, olefin block copolymer: 25 parts, EPDM rubber: 5 parts, wear-resistant agent: 10 parts, modified leather powder: 5 parts, stearic acid: 0.3 parts, zinc stearate: 0.5 parts, zinc oxide: 1.5 parts, odorless bridging agent: 0.5 parts, AC foaming agent: 5.5 parts.
[0107] The preparation method comprises the following steps:
[0108] 1) Weigh the following ingredients by mass: 45 parts of ethylene-vinyl acetate copolymer, 25 parts of polyolefin elastomer, 25 parts of olefin block copolymer, 5 parts of EPDM rubber, 10 parts of anti-wear agent, 0.3 parts of stearic acid, 0.5 parts of zinc stearate, 1.5 parts of zinc oxide, and 5 parts of modified leather powder;
[0109] 2) kneading all the ingredients weighed in step 1) for 5-10 minutes at a temperature of 105-115°C;
[0110] 0.5 parts of odorless bridging agent and 5.5 parts of AC foaming agent were added to the above mixture and then kneaded.
[0111] 3) Granulate the mixture obtained in step 2) for 9-11 minutes at a temperature of 100° C.-105° C. and store for 24 hours for later use.
[0112] 4) pouring the particles obtained in step 3) into a desired small foaming mold for foaming;
[0113] 5) The small foams prepared in step 4) are cleaned and stored for 12 hours, and then placed in an MD molding machine for heating for 420 seconds and cooled for 420 seconds (the temperature of the MD molding machine is 155-165°C, and the cooling temperature is 11-17°C) to obtain an EVA composite foam material MD sole.
[0114] The following table shows the formula of high-resilience environmentally friendly EVA composite foam material MD sole embodiment 1, embodiment 2, embodiment 3, and the formula of conventional lightweight foam MD sole comparative example 1, leather unmodified comparative example 2, and comparative example 3 without adding the modified hydrogenated resin of the present invention:
[0115] Table 1: Formulas of EVA foam materials of various embodiments and comparative examples
[0116]
[0117] Among them, ethylene-vinyl acetate copolymer is EVA7470M, polyolefin elastomer POE is ENGAGE 8150, olefin block copolymer OBC is Infuse9170, EPDM rubber is 3092; the wear-resistant agent is 108E produced by Xiamen Boschyuan Company.
[0118] The physical properties of the EVA foam materials obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 were tested. The results are shown in Table 2. The test conditions were a temperature of 23±3° C. and a humidity of 65±5%.
[0119] Table 2: Physical properties of EVA foam materials of various embodiments and comparative examples
[0120]
[0121] The embodiments of the present invention add modified leather powder and modified hydrogenated resin composite materials, and the comparative examples add conventional polyolefin elastomers. It can be seen from the data in Table 2 that the specific gravity, resilience, wear resistance and delamination of the embodiments are significantly better than those of the comparative examples, and the various data of the embodiments can meet the national standards.
[0122] The foam material was structurally observed, and the results are shown in Figures 1 to 8 .in, Figure 1 , Figure 2 and Figure 3 For Example 1, Figure 4 For comparative example 2, Figure 5 and Figure 6 For Example 2, Figure 7 For comparative example 3, Figure 8 This is comparative example 3. By observing at magnifications of 250X, 500X, 2000X, 8000X, and 20000X, and comparing with the scanning electron microscope (SEM) without adding the modified leather powder, the modified leather powder is tightly combined with the foaming material after being added.
[0123] The above examples are only used to illustrate the technical features and implementation process of the present invention, rather than to limit the technical solution of the present invention. It should be pointed out that for ordinary technicians in this field, the present invention can still be modified or replaced by equivalents, and modifications or replacements that do not deviate from the principles of the present invention are all covered by the protection of the present invention.
Claims
1. A high-resilience environmentally friendly EVA composite foam material, characterized in that: The EVA composite material is prepared by foaming, and the EVA composite material includes the following components in parts by weight: 40-50 parts of ethylene-vinyl acetate copolymer, 15-30 parts of polyolefin elastomer, 10-26 parts of olefin block copolymer, 4-10 parts of EPDM rubber, 5-10 parts of anti-wear agent, 3-5 parts of modified leather powder, 1.5-2.5 parts of modified hydrogenated resin, 0.2-0.5 parts of stearic acid, 0.2-1 parts of zinc stearate, 1.2-2 parts of zinc oxide, 0.3-0.8 parts of odorless bridging agent, 4-6 parts of AC foaming agent; The modified leather powder is obtained by surface-modifying the waste leather powder ground at low temperature with N-aminoethyl-3-aminopropylmethyldimethoxysilane; The modified hydrogenated resin is formed by mixing polyethylene glycol and hydrogenated resin raw materials, and the hydrogenated resin is a hydrogenated C5 petroleum resin; the polyolefin elastomer is an ethylene-α-olefin copolymer elastomer structure, which is an 8C structure composed of ethylene and octene; the olefin block copolymer is composed of a hard segment of crystallizable ethylene-octene and a soft segment of amorphous ethylene-octene.
2. The high resilience environmentally friendly EVA composite foam material according to claim 1, characterized in that: The vinyl acetate content in the ethylene-vinyl acetate copolymer is between 26% and 40%.
3. The high resilience and environmentally friendly EVA composite foam material according to claim 1, characterized in that: The density of the polyolefin elastomer is 0.87-0.91 g / cm 3 .
4. The high resilience environmentally friendly EVA composite foam material according to claim 1, characterized in that: The particle size of the modified leather powder is 120-150 meshes.
5. The high resilience and environmentally friendly EVA composite foam material according to claim 1, characterized in that: The modified hydrogenated resin is formed by mixing polyethylene glycol with a molecular weight of 3000-5000 and a hydrogenated resin raw material in a mass ratio of 0.5-2:1; and the wear-resistant agent is a vinyl silicone composite wear-resistant agent.
6. The high resilience and environmentally friendly EVA composite foam material according to any one of claims 1 to 5, characterized in that: The density of the high-resilience environmentally friendly EVA composite foam material is 0.17-0.20 g / cm 3 , hardness is 45-50 Asker C.
7. The method for preparing the high-resilience environmentally friendly EVA composite foam material according to any one of claims 1 to 6, comprising the following steps: Mixing the components except the odorless bridging agent and the AC foaming agent according to weight fractions to obtain a first mixed product; The first mixed product is mixed with an odorless bridging agent and an AC foaming agent to obtain a second mixed product; After the second mixed product is granulated, the high-resilience and environmentally friendly EVA composite foam material is obtained through an injection foaming process or a secondary compression foaming process.
8. The preparation method according to claim 7, characterized in that: The modified leather powder is obtained by the following operation: using liquid nitrogen to cryogenically freeze and airflow spray waste leather, and then performing cryogenic grinding to obtain waste leather powder; using N-aminoethyl-3-aminopropylmethyldimethoxysilane to perform surface modification on the waste leather powder to obtain the modified leather powder.
9. The preparation method according to claim 7, characterized in that: The secondary compression molding foaming process comprises: performing small foaming on the granulated material according to the mold shape to form a rough blank; hot pressing the rough blank, cooling and shaping it, to obtain the high-resilience environmentally friendly EVA composite foaming material.
10. Use of the high-resilience environmentally friendly EVA composite foam material as claimed in any one of claims 1 to 6 as a midsole in the preparation of shoes.
Citation Information
Patent Citations
EVA foaming composition and preparation method thereof
CN109796668A
Natural aromatic environment-friendly EVA composite foam material and preparation method and application thereof
CN111423653A
Shrinkage-resistant rubber foaming material as well as preparation method and application thereof
CN115926266A
One-step modification method of leather scraps, composite material of leather scraps and application of composite material
CN117624909A
Cited By
High-resilience damping EVA material and preparation method thereof
CN122185667A